2011
DOI: 10.5588/ijtld.10.0681
|View full text |Cite
|
Sign up to set email alerts
|

Sputum induction for microbiological diagnosis of childhood pulmonary tuberculosis in a community setting

Abstract: Sputum induction is feasible and safe in a community setting. Sputum induction was useful for making a microbiological diagnosis, increasing the number of children diagnosed and treated for PTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 0 publications
2
43
0
Order By: Relevance
“…Sputum induction with hypertonic saline was found to be safe and useful for microbiological confirmation of pulmonary TB in both HIV positive and HIV negative children in a study in South Africa: overall, 24% of children had a positive smear or culture for Mycobacterium tuberculosis and induced sputum (IS) samples had a three-times greater yield than gastric lavage (GA), with no difference in yield by HIV infection status [36]. This was later evaluated in the community setting with 16.9% of clinically diagnosed TB cases confirmed microbiologically [37], highlighting the usefulness of this diagnostic tool in the outpatient settings. However the need for electrical supply and special technical equipment, together with the high work load and infectious hazard are substantial obstacles for widespread use of this method.…”
Section: Challenges Of Diagnosis Of Tb In Children With Hivmentioning
confidence: 99%
“…Sputum induction with hypertonic saline was found to be safe and useful for microbiological confirmation of pulmonary TB in both HIV positive and HIV negative children in a study in South Africa: overall, 24% of children had a positive smear or culture for Mycobacterium tuberculosis and induced sputum (IS) samples had a three-times greater yield than gastric lavage (GA), with no difference in yield by HIV infection status [36]. This was later evaluated in the community setting with 16.9% of clinically diagnosed TB cases confirmed microbiologically [37], highlighting the usefulness of this diagnostic tool in the outpatient settings. However the need for electrical supply and special technical equipment, together with the high work load and infectious hazard are substantial obstacles for widespread use of this method.…”
Section: Challenges Of Diagnosis Of Tb In Children With Hivmentioning
confidence: 99%
“…11 However, other groups in South Africa have shown that sputum induction can be used at primary health care settings. 22,23 In contrast, the string test itself is affordable (US$1.00 per test) and requires limited training of nursing staff.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Among children with mild illness admitted to a case-verification ward as part of an infant TB vaccine trial, the yield of a single IS and GL sample was equivalent; however, positive cultures (from 2 GL and 2 IS samples) were only obtained in 10% of children admitted. 25 More recently a study done at a primary care clinic in Khayelitsha, investigated 270 children (median age 38 months) with suspected TB with 2 IS specimens taken on sequential days.…”
Section: Microbiological Diagnosismentioning
confidence: 99%
“…However, several studies done in Cape Town have confirmed the feasibility and usefulness of microbiological confirmation in young children with suspected PTB using sputum induction. [23][24][25][26][27][28] These have shown that collection of sputum is feasible, safe and effective even in infants. Sputum induction has a number of advantages over gastric lavage (GL) as it can be done as an outpatient procedure, is relatively easy to perform, and the yield is higher.…”
Section: Microbiological Diagnosismentioning
confidence: 99%
See 1 more Smart Citation